Spatio‐temporal trends in caries: A study on children in Berlin‐Mitte - Ae Kyung Lee; Annette Aigner; Timo Schmid; Tobias Kurth (Wiley, 2021)
Abstract Background Significant inequalities in caries distribution among children in Germany have been reported, but small‐scale areas remain understudied. Aim To examine spatio‐temporal trends in children's dental caries at the small‐area level in Berlin‐Mitte. Design Routinely collected data from Berlin's annual Health Examination Surveys were used, which also include information on age, sex, country of origin, and residential area. The study population consists of 14,866 children aged 5 to 7 between 2006 and 2014 in the district of Berlin‐Mitte. Outcome variables are the dmft (decayed, missing, and filled teeth), the presence of any caries experience, untreated caries, and caries risk. The outcomes are summarized descriptively and graphically presented for 10 quarters and 41 communities within Berlin‐Mitte. Results Relevant gaps in children's dental caries were discovered between the quarters of Mitte. Three quarters in the northeast part of Mitte have consistently indicated the lowest oral health status in all four outcomes, and children having high caries risk have been increasingly concentrating in this area over time. Despite the continuous improvements in the southern part, the averages in total of Mitte for all outcomes have risen. Conclusion Our findings confirm the spatiotemporally mounting disparities in children's oral health between the quarters in Berlin‐Mitte and that particular quarters need urgent attention. The small‐area approach made it easier and more effective to reveal the spatial distribution of children's dental caries at the local level. The small‐area analysis should be strongly encouraged in future caries research to narrow the inequalities in children's oral health.